2013
DOI: 10.1136/bmjopen-2013-003241
|View full text |Cite
|
Sign up to set email alerts
|

A survey of radiation treatment planning peer-review activities in a provincial radiation oncology programme: current practice and future directions

Abstract: ObjectivesTo describe current patterns of practice of radiation oncology peer review within a provincial cancer system, identifying barriers and facilitators to its use with the ultimate aim of process improvement.DesignA survey of radiation oncology programmes at provincial cancer centres.SettingAll cancer centres within the province of Ontario, Canada (n=14). These are community-based outpatient facilities overseen by Cancer Care Ontario, the provincial cancer agency.ParticipantsA delegate from each radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 23 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…However, across North American academic centres, where one would expect the proportion of RT cases undergoing peer review should be the highest; only 80% of institutions reported peer review of all cases [20]. Similarly, only 4 (29%) of the 14 Ontario RT centres reviewed at least 80% of its radical RT cases, and only 2 other centres (14%) reviewed between 50 and 79% of its cases [13]. Only 5 centres reviewed the treatment plans prior to initiation of therapy, citing the number of ROs present at the time of peer-review as being the most significant rate-limiting step [13].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, across North American academic centres, where one would expect the proportion of RT cases undergoing peer review should be the highest; only 80% of institutions reported peer review of all cases [20]. Similarly, only 4 (29%) of the 14 Ontario RT centres reviewed at least 80% of its radical RT cases, and only 2 other centres (14%) reviewed between 50 and 79% of its cases [13]. Only 5 centres reviewed the treatment plans prior to initiation of therapy, citing the number of ROs present at the time of peer-review as being the most significant rate-limiting step [13].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, only 4 (29%) of the 14 Ontario RT centres reviewed at least 80% of its radical RT cases, and only 2 other centres (14%) reviewed between 50 and 79% of its cases [13]. Only 5 centres reviewed the treatment plans prior to initiation of therapy, citing the number of ROs present at the time of peer-review as being the most significant rate-limiting step [13]. A recent review of the British Columbia Cancer Agency experience over a 6-year period likewise demonstrated that only 13% of all their radical RT cases were in fact reviewed, demonstrating that significant challenges remain in our communities [12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Exposure of trainees to these rounds varies, with one 2013 study in Ontario, Canada noting that of the 14 radiation treatment centres in the province, only 3 (21%) self-reported that trainees regularly attended peer review rounds [17]. It is expected that this number is increasing given the increasing attention in the community to the value of peer review.…”
Section: Discussionmentioning
confidence: 97%
“…There is a growing global recognition of the need for peer review and Brundage et al [16] surveyed 14 radiotherapy departments in Ontario, Canada with detection of errors and improvement in planning process the greatest perceived benefit among respondents. Six centres reviewed at least 50% of curative plans e limitations of radiation oncologist time being the main factor hindering this.…”
Section: Discussionmentioning
confidence: 98%